(untitled) (Research, Society and Development, 2020)
This article presents reflections on teacher training to work in Basic Education (EB), based on the discourses of the National Curriculum Guidelines (DCN) of 2002, 2015 e 2019. It aims to highlight contradictions present in the DCN and its implications for the training of EB teachers, contributing to the debate on training teachers in Brazil. The research was oriented by the Historical-Dialectic Materialism, mainly, about the authors Bazzo & Scheibe (2019), Kuenzer (2016), Curado Silva (2017), Aguiar & Dourado (2018), Duarte (2003), among others. It was possible to perceive that the current DCN for teacher training, despite using words that refer to critical perspectives, its essence is the resumption of capitalist reconfiguration as in the 2002 DCN. It is hoped that this study contribute to the teacher training aiming at emancipated human beings. We emphasizes that this subject is recent, so we believe more researchs are still needed to understand the impact of the new DCN for teacher training and their job.